(untitled) (International Research in Economics and Finance, 2022)
The widespread use of big data technology has brought various convenience to enterprise management, and the application of big data technology to the performance management segment can promote enterprises to further deepen the reform, help the organizational structure of enterprises to be optimized and employees’ abilities to be fully exploited, and promote enterprises to gain advantages in market competition and move forward in the competition of creating value for organizations and society in the new era. This paper firstly elaborates the three core dimensions of enterprise performance management, then studies the current situation of performance management in Chinese enterprises, and proposes corresponding innovative solution strategies for enterprises to integrate big data technology into performance management.